PEMIKIRAN TEOLOGIS EDUKATIF YOHANES CALVIN SERTA RELEVANSINYA BAGI PENDIDIKAN BERGEREJA MASA KINI - Tulung, Jeane Marie; Masinamboue, Yornan (Tumou Tou, 2020)
The purpose of this paper is to describe and understand how the thought of John Calvin who was a famous reformer figure from time to time. Calvin paid great attention to Christian education especially in the church. He arranged systematically the way, the content of the teaching, as well as the qualifications, self-image of the teachers both pastors and religious teachers who were all based on the Bible and to glorify God. The method used in this paper is a qualitative research method with a literature study study in which the researcher reviews, compares, formulates and analyzes Calvin's thoughts both in his life context, his thoughts through books, documents, journals and other relevant literature studies. From the findings it can be said that Calvin's educative theological thought is purely based on the Bible. For Calvin, the teaching of the Christian faith is determined by the Bible and interpretations that are right and right and can have a good influence on the church and society. Calvin is always thinking of the right way so that the quality of the faith of the congregation continues to develop well and can be implemented in a variety of social life. In the midst of challenges today the church is required not to be carried away by various kinds of ideas that do not emphasize the Bible as the basis of human life. As it was done, Calvin the priests, teachers of religion today are required with full responsibility to think deeply about ways to continue to nourish the true Christian faith based on the Scriptures so that the quality of their faith is well preserved and lives glorifying God.